123I-iomazenil whole-body imaging to detect hepatic carboxylesterase drug-metabolizing enzyme activity. Issue 9 (September 2018) - Mizutani, Asuka; Kobayashi, Masato; Fujita, Ken-ichi; Takahashi, Kotaro; Hokama, Tsuzumi; Takasu, Hiroaki; Nishi, Kodai; Nishii, Ryuichi; Shikano, Naoto; Fukuchi, Kazuki; Kawai, Keiichi
Abstract : Objectives: Drugs are mainly metabolized by hepatic enzymes, the activity of which can differ between individuals. Although it is ideal to measure the hepatic clearance of liver-targeted drugs in individualized medicine, blood enzyme tests typically measure metabolic drug clearance in the entire body, and not just in the liver. We investigated whether 123 I-iomazenil imaging can directly assess and quantify the activity of hepatic drug-metabolizing enzymes. Materials and methods: Hepatic enzymes that metabolize 123 I-iomazenil were identified by thin-layer chromatography in mouse liver homogenates with bis(4-nitrophenyl) phosphate (BNPP) inhibitor for carboxylesterase enzymes and nicotinamide adenine dinucleotide phosphate (NADPH) generator for cytochrome P450 enzymes. Whole-body images of mice were acquired using 123 I-iomazenil with and without BNPP, and the distribution was also obtained. The metabolism of 123 I-iomazenil in the blood, liver, gall bladder, and bladder was investigated by thin-layer chromatography. Results: From the in-vitro metabolism of 123 I-iomazenil using BNPP, the enzyme converting 123 I-iomazenil to 123 I-R-COOH was identified as carboxylesterase, and that converting 123 I-iomazenil to M2 was identified as cytochrome P450 in experiments with and without an NADPH generator. The biological distribution and whole-body imaging showed increased accumulation in the liver of mice administered BNPP compared with normal mice, but decreased levels in the gall bladder and small intestine. The main fraction in bile and urine was 123 I-R-COOH, with two unknown metabolites (M1 and M2), 123 I −, and 123 I-iomazenil also being present. Conclusion: 123 I-iomazenil whole-body imaging has good possibility of direct measurement of hepatic carboxylesterase activity as accumulation of 123 I-R-COOH in the gall bladder through bile and in the bladder through urine. Abstract : Supplemental Digital Content is available in the text.